Reingeniería de procesos de la empresa A.W.T. S.A. de la ciudad de Quito - Ortega Guanuchi, Tania Ximena (2016)
Business Process Reengineering is a modern management tool towards processes improvement. A successful application followed by innovation and continuous improvement allows us to remain competitive, yet this application by itself cannot solve organization´s problems or flaws. Business Process Reengineering is a fast, short and offers radical changes. In order to generate processes efficiently to finally obtain an optimal product. Talking about a great change that any institution or organization is waiting for and wouldn´t doubt to apply it; therefore this is the reason that the following work entitled “REINGENIERÍA DE PROCESOS DE LA EMPRESA A.W.T. S.A. DE LA CIUDAD DE QUITO” is looking for to establish new internal policies and business processes. Statistical method: Use it when making surveys to 93 internal customers and 10 external customers and company´s manager interview Analytical method: we proceed to analyze each business process. Inductive method: throughout deduction critical data was obtained. Survey technique: a survey using a sample of 93 internal customers and 10 external customers. Observation technique: with this technique it´s known in detail the development and implementation of each process. Interview: information was compiled by a conversation with company´s manager. Literary Review: Important aspects are well known to get to know about some of their products and equipment used to purify water; referring to process reengineering with their advantages and disadvantages of cours